The Role of Career Development and Commitment to Mediate the Effect of Competence on the Employees Performance in Dinas Kependudukan & Pencatatan Sipil Kabupaten Sidoarjo - Odelia, Evi Maya; Hendrati, Ignatia Martha; Anwar, Muhadjir (Universitas Nahdlatul Ulama Blitar, 2023)
This study aims to determine and analyze the influence of the effect (1) competence on employee performance, (2) competence mediate career development on employee performance, and (3) competence mediate commitment on employee performance at Dinas Kependudukan & Pencatatan Sipil Kabupaten Sidoarjo. This is quantitative research of the associative variety. All civil servants at the Dinas Kependudukan & Pencatatan Sipil in Kabupaten Sidoarjo were included in the sample with saturation sampling approach. Forty-four civil servants were surveyed using questionnaires to collect the data. The quantitative data analysis technique uses PLS (Partial Least Square) with smartPLS 3.0 software.Â This research at the Dinas Kependudukan & Pencatatan Sipil Kabupaten Sidoarjo as a government agency in the field of public services in improving the performance of its employees by providing competency, career development and commitment to civil servants of Dinas Kependudukan & Pencatatan Sipil in Kabupaten Sidoarjo. The results indicated that competence has a significant positive effect on employee performance, career development has a non-significant effect in mediating competence's effect on employee performance, and commitment has a significant positive effect in mediating competence's effect on employee performance.